(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The border between palliative sedation and euthanasia is important to distinguish a right from a crime; a good clinical practice from improvidence, negligence, carelessness, abuse. Palliative care indeed refuses euthanasia, in the sense of the intentional killing by act or omission of a dependent human being for his or her alleged benefit (definition by Council of Europe), provides relief from pain and other distressing symptoms and affirms life and regards dying as a normal process; intends neither to hasten or postpone death (according to the definition of the WHO). Italian National Bioethics Committee, aware of the importance of the border with euthanasia, has proposed the definition of continuous deep palliative sedation in the imminence of death. Not so the new French law, which has legalized deep and continues sedation until death, in a context where the physicians can interrupt any treatment, including basic care such as artificial nutrition and hydration, if it could be interpreted as unreasonable obstinacy, even if the patient is unconscious and he or she isn’t at the end of the life but he or she is living “an artificial life”. The author explains how France, in this way, has effectively legalized euthanasia. Finally the a. analyses legislative proposals being examined by Italian Parliament regarding the choice between euthanasia and palliative care.